Char Davies's Immersive Virtual Art and the Essence of Spatiality - McRobert, Laurie (Book collections on Project MUSE., 2007)
In this first book-length study of the internationally renowned Canadian artist Char Davies, Laurie McRobert examines the digital installations Osmoseand Ephemerein the context of Davies' artistic and conceptual inspirations. Davies, originally a painter, turned to technology in an effort to create the effect of osmosis between self and world. By donning a head-mounted display unit and a body vest to monitor breathing and balance, participants are immersed in 3D-virtual space where they interact with abstract images of nature while maneuvering in an artificial spatial environment. Char Davies' Immersive Virtual Art and the Essence of Spatiality explores spatiality through a broad scope of disciplines, including philosophy, mythology, biology, and visual studies, in order to familiarize the reader with virtual reality art -- how it differs from traditional artistic media and why immersive virtual art promises to expand our imaginative horizons. This original study provides us with an important exposition of two of Char Davies' acclaimed projects and an exploration of the future impact of digital virtual art on our worldviews. -- Publisher description.